2015
DOI: 10.1007/s13311-015-0358-6
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Conditioning Is Safe and Effective for Octo- and Nonagenarians in Stroke Prevention and Treatment

Abstract: Symptomatic intracranial arterial stenosis (SIAS) is very common in octo-and nonagenarians, especially in the Chinese population, and is likely the most common cause of stroke recurrence worldwide. Clinical trials demonstrate that endovascular treatment, such as stenting, may not be suitable for octogenarians with systemic diseases. Hence, less invasive methods for the octogenarian patients are urgently needed. Our previous study (unique identifier: NCT01321749) showed that repetitive bilateral arm ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
199
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(205 citation statements)
references
References 45 publications
6
199
0
Order By: Relevance
“…More study is needed. Although the overall findings of Meng et al [7] and others are consistent with data from animal models and are promising, the translation into a possible clinical benefit remains to be shown in large phase III trials. In addition, the optimal timing, frequency, and duration of rIPC need to be better defined.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…More study is needed. Although the overall findings of Meng et al [7] and others are consistent with data from animal models and are promising, the translation into a possible clinical benefit remains to be shown in large phase III trials. In addition, the optimal timing, frequency, and duration of rIPC need to be better defined.…”
supporting
confidence: 53%
“…The studies of Meng et al and others [5][6][7] indicate that rIPC holds promise as a simple and easy neuroprotective strategy for a large number of stroke patients. It is suited for 1) primary and secondary stroke prevention in multiple settings, including symptomatic and asymptomatic intra-and perhaps extracranial arterial occlusive lesions; 2) as an adjunctive strategy with or without reperfusion therapy for acute ischemic stroke; and 3) as a prophylactic strategy against delayed ischemic injury in subarachnoid hemorrhage.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Improvement in event-free survival in the group that received repeated RIPC was recently reinforced by another study from the same group. In that study, significant protection against stroke recurrence was observed after 180 days of twice daily RIPC in symptomatic intracranial arterial stenosis patients (Meng et al 2015). Another recent study examined the impact of repeated RIPC on diabetic wound healing in patients with diabetes mellitus type 1 or type 2 (Shaked et al 2015).…”
Section: Impact Of Repeated Ipc: Clinical Outcomesmentioning
confidence: 95%
“…The efficiency of remote ischemic conditioning (consisting in brief ischemic episodes induced in the lower or upper limb by cyclic cuff inflation and deflation) in the prevention of stroke recurrence in patients with symptomatic intracranial arterial stenosis has been tested with supportive results. 51,52 Postconditioning might be a useful paradigm in a rehabilitative perspective but remains to be evaluated in humans. Results of remote ischemic postconditioning in patients at an acute phase of ischemic stroke, alone or as an adjunct therapy to conventional fibrinolysis, are encouraging.…”
Section: Brain Hypoxic Conditioning In Humans Strokementioning
confidence: 99%